Validating Marital Commitment Inventory in Iranian state university students - Khorasaniyan, Mojghan (International Journal of Education and Cognitive Sciences, 2022)
This research was performed in order to validate the Marital Commitment Inventory among the students of Iran’s state universities which were selected by. The inventory was constructed via Delphi technique based on Johnson’s theoretical framework. It had 37 items and 2 additional items for detecting lies. In this way 500 persons were selected from the statistical population by employing multi cluster sampling. After that exploratory factor analysis was applied for assessing factor structure and construct validity of the inventory. Results: The outcomes realized that 12 out of 37 items were excluded because of meaningless factor loadings and there only stood 25 items. In order to inspect the residual items the confirmatory factor analysis was performed and approved the 25-item inventory with 6 subscales, including: social, personal, gratifying, moral, cultural, and logical- intuitive commitment. Except of the gratifying subscale which holds only 2 items, other subscales include at least 3 items. Using Cronbach’s alpha co-efficient the reliability of the residual items was confirmed. Multivariate Analysis of Variance (MANOVA) and Wilks Lambda were applied to compare the differences between bachelor and married students, and also female and male students. It represented that the average scores of the cultural subscale in married students are meaningfully higher than those of the bachelors. Besides it realized that the average scores of male students are meaningfully higher in moral and logical- intuitive subscale. Also female students have meaningfully higher scores in cultural subscale.